PENDIDIKAN WIRAUSAHA BERLANDASKAN TRI HITA KARANA MENUJU KEBERKELANJUTAN USAHA - Apriani, Luh; Suastika, I Nengah; Lasmawan, I Wayan (STKIP Persada Khatulistiwa Sintang, 2023)
This article discusses the importance of entrepreneurship education based on the Tri Hita Karana concept, a Balinese Hindu philosophy emphasizing balance and harmony in three key aspects: the relationship between humans and the divine (Parahyangan), the relationship between humans (Pawongan), and the relationship between humans and nature (Palemahan). This approach integrates local cultural values, promotes collaboration and solidarity, emphasizes environmental sustainability, and encourages creativity and innovation in business. The article also addresses elements of business ethics, including integrity, community spirit, accountability, and transparency, which play a vital role in guiding entrepreneurs' behavior. This holistic approach creates entrepreneurs who are not only financially successful but also socially and environmentally responsible, with a strong ethical foundation in entrepreneurship. By incorporating the Tri Hita Karana concept into entrepreneurship education, it can nurture entrepreneurs who seek not only personal profit but also contribute to the well-being of society and environmental sustainability. Entrepreneurship education based on Tri Hita Karana is a step towards more meaningful and sustainable success for individuals and communities